[Rocky Island on Shore of Heimaey] - Streng, Evelyn Fiedler (1975)
Photograph of rock islands along the shore of Heimaey. A large, grass covered rock pillar stands tall in the water to the left. A much smaller island is visible to the right ahead of the large, grassy cliffs in the background. Three heads of people are visible in the bottom left corner of the photograph along the grey water. The sky is cloudy and dark at the top of the photograph